2019
DOI: 10.1007/s13593-019-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Legume-based rotations have clear economic advantages over cereal monocropping in dry areas

Abstract: Current land use trends show an increasing preference for monocroppingmostly a consequence of policies and incentives aimed at enhancing the intensification of cereals. This shift has caused some to question whether legume-cereal rotations can remain economically viable options for farmers, particularly in the dry areas. In this paper, we present the results of an endogenous switching regression model which suggests, for the first time, that legume-cereal rotations have clear economic advantages over cereal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Rotation results in a positive and significantly higher yield from the subsequent wheat crop, consistent with the ecological benefits of the faba‐bean–wheat rotation and the findings of Yigezu et al. (2019).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Rotation results in a positive and significantly higher yield from the subsequent wheat crop, consistent with the ecological benefits of the faba‐bean–wheat rotation and the findings of Yigezu et al. (2019).…”
Section: Resultssupporting
confidence: 87%
“…The use of improved varieties and certified seeds also leads to higher yields relative to the use of local (and old improved) varieties and uncertified seeds for both fields on which ZT is adopted and not adopted—showing clear advantages to the use of both improved varieties and certified seeds, consistent with the findings of Yigezu et al. (2019).…”
Section: Resultssupporting
confidence: 85%
“…These rotations were designed for livestock requirements and because there is an economic use for the crops, but farmers may not necessarily consider soil fertility. Yigezu et al [56] reported that cereal-faba bean rotations provided yields 459 kg.ha −1 (48%) higher than those of monocropped wheat and increased the gross margin for the subsequent wheat crop by MAD1258.ha −1 (i.e., US$146.ha −1 ). The wheat-faba bean rotation increases agricultural income and food security of the household.…”
Section: Potential Impacts Of Current Agricultural Practices and Management Of Organic Input Flows On Soil Fertilitymentioning
confidence: 99%
“…The high returns to investment in wheat are well-documented (Lantican et al, 2016). Some studies also suggest combining this varietal replacement with changing crop water and fertilizer management (Komarek et al, 2017;La Rovere et al, 2014) or rotations (Yigezu et al, 2019).…”
Section: Crop Sciencementioning
confidence: 99%